2017
DOI: 10.21037/jgo.2017.01.13
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory bowel diseases activity in patients undergoing pelvic radiation therapy

Abstract: Background: Few studies with contradictory results have been published on the safety of pelvic radiation therapy (RT) in patients with inflammatory bowel disease (IBD).Methods: From 1989 to 2015, a single center retrospective analysis was performed including all IBD patients who received pelvic external beam radiation therapy (EBRT) or brachytherapy (BT) for a pelvic malignancy. Treatment characteristics, IBD activity and gastrointestinal (GI) toxicity were examined.Results: Overall, 28 patients with Crohn's d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 19 publications
(25 reference statements)
0
17
0
Order By: Relevance
“…Two previously published cohorts displayed high rates of IBD activity after abdominal or pelvic irradiation. Among 28 IBD patients coming from a singlecentre experience who were irradiated from 1989 to 2015, for prostate, rectum or cervix cancer, half of them experienced an IBD flare within the first 6 months 15 . In another multicentre cohort of 47 IBD patients irradiated for prostate cancer, rate of IBD flare was double than that in IBD patients with cancers treated without radiotherapy 16 with highest risk within the first 6 months after radiotherapy.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Two previously published cohorts displayed high rates of IBD activity after abdominal or pelvic irradiation. Among 28 IBD patients coming from a singlecentre experience who were irradiated from 1989 to 2015, for prostate, rectum or cervix cancer, half of them experienced an IBD flare within the first 6 months 15 . In another multicentre cohort of 47 IBD patients irradiated for prostate cancer, rate of IBD flare was double than that in IBD patients with cancers treated without radiotherapy 16 with highest risk within the first 6 months after radiotherapy.…”
Section: Discussionmentioning
confidence: 98%
“…Indeed, few data are available so far on short and long‐term safety of radiotherapy in patients with IBD. Two recent studies suggested a high rate of disease flare after abdominal or pelvic radiotherapy in IBD patients; but these results are hampered by small numbers and lack of evaluation of disease activity before radiotherapy 15,16 …”
Section: Introductionmentioning
confidence: 99%
“…Many studies have attempted to assess the safety of RT in patients with IBD [ 5 , 7 , 8 , 11 ]. An examination of the correlation between pelvic RT and IBD patients showed that only the patients with a rectal IBD location or a low body mass index had experienced more severe IBD activity within or after 6 months following the RT [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have attempted to assess the safety of RT in patients with IBD [ 5 , 7 , 8 , 11 ]. An examination of the correlation between pelvic RT and IBD patients showed that only the patients with a rectal IBD location or a low body mass index had experienced more severe IBD activity within or after 6 months following the RT [ 11 ]. A study assessing IBD-specific outcomes in 100 veterans with IBD revealed that the rates of IBD-associated hospitalizations and IBD-related surgeries were not significantly different between those treated with or without radiation, and there was no effect of radiation on longer-term outcomes [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, acute GI toxicity of grade 2 or higher is exacerbated in patients undergoing concomitant medical therapy for IBD [7]. Advances in modern RT have demonstrated a trend toward improved toxicity profiles from treatment in high-risk groups such as patients with IBD [8,9].…”
Section: Purposementioning
confidence: 99%